2000
DOI: 10.2527/2000.7861458x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of horses to 24 hours of transportation using a commercial van during summer conditions.

Abstract: Fifteen mature horses (mares, n = 6); geldings, n = 9) were used to assess the physiological responses of 24 h of transport in a commercial van under California summer conditions. The study was conducted on four consecutive days, and data were collected on d 1 and d 2 to obtain baseline values and to determine any diurnal variation in the individual measurements. Travel commenced on d 3 at 0800 for 24 h, with a total of 1,622 km traveled. Blood samples were collected at 0800, 1100, 1400, 2000, and 0200 each da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
101
5
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 11 publications
16
101
5
6
Order By: Relevance
“…The physiologic responses of horses to short road transport show a decrease in BW (although not significant), as confirmed by a negative correlation only between BW and T 3 , as well as an increase in rectal temperature, in accordance with that reported after long, medium and short trips (Waran et al, 1996;Stull, 1999;Stull and Rodiek, 2000). However, no differences were observed relating to different ages.…”
Section: Discussionsupporting
confidence: 85%
“…The physiologic responses of horses to short road transport show a decrease in BW (although not significant), as confirmed by a negative correlation only between BW and T 3 , as well as an increase in rectal temperature, in accordance with that reported after long, medium and short trips (Waran et al, 1996;Stull, 1999;Stull and Rodiek, 2000). However, no differences were observed relating to different ages.…”
Section: Discussionsupporting
confidence: 85%
“…We did not evaluate the changes of cortisol, leukograms, and PMN cell functions after transportation. In terrestrial mammals, these parameters are recovered to a level before transportation within a week at most [15,22,27]. These reports showed that immunological uncertainty followeding transportation would enhance the potential risk of infectious disease in susceptible individuals.…”
Section: Discussionmentioning
confidence: 89%
“…The observed changes in phagocytosis and NBT reduction were correlated with alterations in circulating concentrations of cortisol induced by the stress of handling and transportation. Elevated serum cortisol concentrastions and changes in immune systems have been reported associated with the transportation of terrestrial mammals [22,27,30]. There are few reports on the effects of stress on PMN cell functions, however, Dixit et al [7] reported that stress was correlated with neutrophil functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transit from 50 to 500 km significantly changed the cortisol release ratio, however, it did not influence plasma or salivary cortisol levels determined immediately after unloading (Fazio et al 2008, Schmidt et al 2010c. A 24 hour resting period after 24 hours of transport was generally sufficient to restore the plasma cortisol concentration to initial levels, even on a summer day, with maximal environmental temperature exceeding 38°C (Fazio et al 2008b, Stull et al 2008, Stull and Rodiek 2000. Moreover, Schmidt et al (2010a,b,c) stated that salivary cortisol concentration in experienced horses decreased after transport to baseline values within 30 min, and in naïve horses, within three hours.…”
Section: Introductionmentioning
confidence: 99%